Precision asphere polishing with MRF technology and Subaperture Stitching Interferometry - Gogler, Slawomir; Bieszczad, Grzegorz; Krupiński, Michał (Photonics Letters of Poland, 2013)
The paper presents results of aspheric lens manufacturing in Infrared Technology and Thermovision Section in Military University of Technology. Briefly MRF and SSI technologies utilized in the process are described and a case study of three aspherization processes follows. First two elements are silicon lenses designed for a mid-wave infrared (MWIR) lens. The third one is a parabolic mirror substrate. Technical aspects and requirements of each case are discussed. Full Text: PDF References Forbes, G. W., "Shape spcecification for axially symmetric optical surfaces", Optics Express, Vol. 15, Issue 8, pp. 5218-5226 (2007) CrossRef